Relationship between academic self-concept, causal attribution for success and raílure, - Moreano, Giovanna (2005)
Relationship between academic self-concept, causal attribution for success and raílure, and academic achievement in pre-adolescents. This study shows the relationship between the variables mentioned above in 284 primary school students in Lima (5"' aI)d 6"' grades). The Self Description Questionnaire (SDQ-I) and the Sydney Attribution Scale (SAS) were applied with a previous validation process. Mathematics and Language final grades were assumed as academic achievement indicators. SAS exploratory factorial analysis showed five factors, tbree of them demonstrated that children do not discriminate between effort and ability. About SDQ, results confirmed that children can differentiate between self-concept dimensions. Participants showed a favorable self-concept in a11 dimensions and a strong intemal locus of control. In the same way, there was a tendency for studems to accept success for internal causes and totally deny failure.